The Socio-Economic Structure of Large Villages in the Southern Levant During the Chalcolithic Period: A View from the Eastern Mediterranean Coast - Varga, Daniel; Pasternak, Martin David; Abadi-Reiss, Yael (Antiguo Oriente, 2026)
During the Chalcolithic period, before the rise of urbanism in the Early Bronze Age, large agricultural villages thrived in the Southern Levant. The recently intensively excavated site of “Agamim,” near the Mediterranean coast, provides a case study for understanding economic and social characteristics of the Chalcolithic period. This single-period site, sealed by approximately two meters of soil, contains five settlement layers. Notably, there is a clear separation of architectural spaces based on their uses at Agamim village. These spaces exhibit distinct construction styles, differing material culture, and contrasting trends of continuity across various phases of built areas. The site reflects a complex social system, one that required and facilitated public structures and distinct functional divisions between different areas of the settlement. Agamim is part of the Ghassulian cultural sphere, the dominant entity of the Chalcolithic period, and it encapsulates the rise and decline of that protohistoric era in the southern Levant over approximately 600 years of habitation.